A TEAM DEVELOPMENT EXERCISE - Taylor, John; Miles, Di; Eastgate, John (Groupwork)
This article describes the efforts of three authors to assist the staff of a large children’s home. The exercise attempted to offer an understanding of how behaviour as a group affects the ability of staff to do their jobs and how they might develop ways of using t hose group processes to their advantage.